A social economic study of a Chinese new village / Lim Aik Soon - Lim , Aik Soon (1983)
Chinese new village is· an area of study that is so very often neglected by both researchers local and foreign. This study seeks to study a few socio-economy aspects that is present in a Chinese new village. This new village is situated in Selangor. The· study also strives to find out the factors stimulating the development of this new village. Moreover, it also seek to study the values the residents of this particular new village attached to their jobs, education and other aspects of socio-economy. Finally, it also compares the new village of yesterday with that of today to see the difference between them and to detect the changes going on.